ANALISIS PENGGUNAAN KATA SERAPAN ASING DALAM BERITA ONLINE - Nur Apriliani Pratiwi; Sabdariah (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the use of foreign loanwords in online news articles. The data were collected from ten news items published on three national online portals: Kompas.com, Detik.com, and CNN Indonesia. The study employs a literature review method combined with content analysis using a descriptive qualitative approach. The findings reveal that foreign loanwords—mainly from English—are frequently used in technology, economics, and lifestyle news categories. The types of loanwords identified include loanwords, calques, hybrids, and foreign acronyms. Several terms also undergo spelling adjustments and morphological changes to align with Indonesian language conventions. The use of foreign loanwords functions to enhance communication efficiency, reflect modernity, and fill lexical gaps within Indonesian vocabulary. These findings indicate that digital media play a significant role in disseminating foreign terms and shaping linguistic practices in society.